Analysis of the use of cupola furnace slags, green sand and reclaimed asphalt pavement in asphalt concrete mixtures for low intensity traffic - Vega-Zamanillo, Ángel; Calzada-Pérez, Miguel Ángel; Lastra-González, Pedro; Indacoechea-Vega, Irune; Fernández-Ortega, José Ángel (Revista de la Construcción. Journal of Construction, 2017)
This paper presents the performance of different types of asphalt mixtures containing reclaimed asphalt pavement (RAP) and industrial by-products such as cupola furnace slags and green sands. In this study, conventional bitumen is employed as binding material while limestone is used as natural aggregate. The Marshall method has been used for designing the asphalt mixtures and voids percentage while water sensitivity and wheel tracking tests have been carried out to evaluate the mixtures performance. Although the only natural aggregate is limestone, and this significantly hinders the performance of these mixtures, laboratory results show that they can be successfully employed in the construction of low traffic intensity roads as binder course.